1ISG-001 Health utilities in chronic hepatitis C patients one year after successful treatment with direct-acting antivirals. (March 2019) - Juanbeltz, R; Goñi-Esarte, S; Martínez-Baz, I; San Miguel, R; Zozaya, JM; Rivero, M; Herrero, I; Larrayoz, B; Sarobe, M; Castilla, J
Abstract : Background: Health utilities are measures of quality of life, which are used to obtain quality-adjusted life years in pharmacoeconomic evaluations. A short-term utility improvement has been recently reported after hepatitis C viral clearance, although scarce data exists regarding the long-term variation of these parameters. Purpose: To assess the change in health utility values for patients cured of hepatitis C virus infection, one year after successful treatment with direct-acting antivirals, and the variables associated to that change. Material and methods: Observational, prospective study included cured patients with oral direct-acting antivirals between May 2016 and April 2017. The EQ-5D-5L questionnaire was used to obtain utilities, previous therapy and one year after its end (post48). Differences in the utility medians were compared using the Wilcoxon test. The percentage of disutility reduction was obtained as (post48 – baseline)/(1-baseline)×100. Multivariable linear regression analysis was carried out, adjusting by sex, age, HIV co-infection, baseline limitation of mobility, anxiety-depression and degree of liver fibrosis before treatment. Outcome variable was the difference post48 – baseline utility value. Results: One hundred and ninety-nine patients were enrolled, 65% male. Cirrhosis was present in 29% of the patients and HIV co-infection in 32%. Globally, median health utilities increased from 0.857 at baseline to 0.932 at post-48 (+0.075, p<0.001). In HIV co-infected patients, utilities increased from 0.871 to 0.932 at post 48 (+0.061, p=0.001) and in cirrhotic patients from 0.809 to 0.890 (+0.081, p<0.001). This improvement supposed a whole reduction in disutility of 52%: 47% in HIV co-infected and 42% in cirrhotic patients. In multivariate analysis, moderate-advanced fibrosis (F2–F3) and cirrhosis were associated with higher utility improvement than those with lower fibrosis degree (β=0.06; 95% CI, 0.001 to 0.12 and β=0.07; 95% CI, 0.003 to 0.13, respectively). Conclusion: A long-term improvement in health utilities occurs in chronic hepatitis C patients successfully treated with direct-acting antivirals, even in HCV/HIV co-infected. This benefit is especially evident in patients with advanced fibrosis. The availability of utility values obtained directly from treated patients contributes to future economic evaluations of these new drugs. References and/or acknowledgements: EIPT-VHC project funded by the Spanish Ministry of Health and Carlos III Institute of Health. Conflict of interest: Corporate-sponsored research or other substantive relationships: Regina Juanbeltz has received funding from the Carlos III Institute of Health with the European Regional Development Fund (CM17/00095).